Syntactic Awareness of Indonesian Preschool Students - Teja Komara (Passage, 2016)
This study aims to investigate syntactic awareness of word order changes in the categories of verbal structures and the effects of bilingualism and birth order in relation to syntactic awareness. Employing a mixed method (qualitative and quantitative), data were collected in three ways: 1) visual and audio tasks tapping identification and correction, 2) questionnaires for parents to give information on their children’s backgrounds such as bilingualism and birth order, and 3) observation during the task execution by using recorders for response time and production findings. Nineteen kindergarteners aged 5 and 6 years old participated in a kindergarten in North Bandung. The results reveal that syntactic awareness of word order changes has emerged among the preschool students. The high results can be interpreted in four factors: language-specific characteristics, children’s sensitivity to the larger meaning, innateness/competence, and props. For the categories of ditransitive and transitive, syntactic awareness indicates that the more complex the structures are, the more difficult they are to understand. The implication of the result also reveals that the discrepancy between syntactic knowledge and syntactic awareness may have something to do with the separate position between acquisition and metalinguistic awareness. Also, reading is not the necessary precondition for syntactic awareness of word order change. In the end, the findings on the external factors such as bilingualism and birth order do not seem to affect syntactic awareness performance.Keywords: metalinguistic awareness, syntactic awareness, factors of syntactic awareness, preschool students, linguistic knowledge